The rights of prisoners in places of deprivation of liberty and compliance with international obligations (Journal of actual problems of jurisprudence, 2022)
Today, a lot of work has been carried out and continues in Kazakhstan on the humanization of criminal legislation, improvement of the legislative framework. Increasingly, we have begun to practice the application of international legal standards in the penitentiary system of the Republic of Kazakhstan, which has a positive effect on ensuring the rights and freedoms of persons in places of deprivation of liberty. In recent years, many legislative acts have been reformed, including the Criminal Code of the Republic of Kazakhstan, the new version of the Penal Enforcement Code of July 5, 2014, which entered into force on January 1, 2015, is a definite step in improving the social sphere. The amendments are aimed at improving the procedure and conditions for the execution of criminal penalties, at the same time, the new version of the penal enforcement legislation as a whole has preserved the continuity of the ongoing penal enforcement policy, and timely introduced a number of objective amendments that take into account the most important vectors of further development of the penitentiary system, as well as real opportunities for the implementation of the goals of punishment and the principles of the penal enforcement law of the Republic of Kazakhstan based on international legal norms and compliance with international obligations. The article discusses the issues of guaranteeing the rights of persons serving sentences, and offers recommendations on introducing additional norms into some legislative acts.Keywords: penitentiary system, international standards, convicts, international obligations.